Remote sensing data and their use in topoclimate study - Vysoudil, Miroslav (Journal for Geography, 2007)
This work demonstrates the potential of using current digital satellite raster data to study a topoclimate. Also presented are digital vector data. All data have been provided by the Canadian Center for Remote Sensing in Ottawa within the scope of the solution for the project titled “Environmental Consequences of Local Climatic Effects” (A Case Study: British Columbia). The model region represents the southwest part of British Columbia located between Vancouver and the Okanagan basin. The most valuable components of a topoclimatic research are altimetric data assisting in the calculation of a DEM, multi-spectral images assigned to appropriate land cover categories, and thermal images. Subsequent integration of the DPZ and vector data provides a powerful tool for solving tasks leading to a topoclimate description, potential climatic effects and in wider implications even for studies of their impacts on the living environment.
Keywords: topoclimate; remote sensing; thermal imagery; land cover; DEM